Follow The Money: Piracy and Online Advertising - Michail Batikas; Jörg Claussen; Christian Peukert (International Telecommunications Society (ITS), 2017)
Online copyright enforcement, in the form of either direct action against the supply- side (via website shutdowns) or the demand-side (via individual lawsuits against users), has not been very effective in reducing piracy. Regulators have therefore put forward the so called “follow the money" approach. Because the main source of revenue for infringing websites often comes from online advertising, the idea is that cutting access to advertisers could lower the financial incentives for website owners. In this paper, we aim to provide systematic evidence on the effectiveness of such a policy. We collect data on the advertising services associated with a large number of piracy websites and corresponding set of legitimate " websites before and after the _rst steps of a self-regulatory effort in the European Union went in place. Preliminary results suggest that advertising services indeed reduce their activities on piracy websites, however only those that are most likely to be directly affected by the regulation. We further provide evidence that some advertising services that did not cater to the piracy market before, start to do so perhaps as a strategic response.
Keywords: L82; M37; D83; 330; Piracy; Copyright Enforcement; Online Advertising